2005
DOI: 10.7773/cm.v31i4.31
|View full text |Cite
|
Sign up to set email alerts
|

Two opposite cases of metal accumulation in ria sediments: Ferrol and Corme-Laxe (Galicia, NW Iberian Peninsula)

Abstract: Ciencias Marinas (2005) AbstractThe accumulation of heavy metals (Cd, Cu, Pb and Zn) in surface sediments (<63 µm) of the Ferrol and Corme-Laxe rias was studied. These two rias have opposite characteristics from the point of view of both the morphology and the anthropogenic impact. Low metal concentrations were found in the Corme-Laxe Ria, with the highest values observed in the Anllóns River estuary, probably due to a higher lithogenic composition of the sediments. Concentrations in the Corme-Laxe Ria (Cd, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
2
5
0
1
Order By: Relevance
“…In the estuary, their NEFs were slightly higher, probably resulting from some contamination in the area or just a difference in the lithogenic composition of the riverine sediments, which are naturally richer in metals as has been reported for other Galician Rias (e.g. Cobelo-Garcia et al, 2005). For Pb, the average NEFs are indicative of a null/low contamination both in the ria and estuary.…”
Section: Background Values and Enrichment Factorsmentioning
confidence: 72%
“…In the estuary, their NEFs were slightly higher, probably resulting from some contamination in the area or just a difference in the lithogenic composition of the riverine sediments, which are naturally richer in metals as has been reported for other Galician Rias (e.g. Cobelo-Garcia et al, 2005). For Pb, the average NEFs are indicative of a null/low contamination both in the ria and estuary.…”
Section: Background Values and Enrichment Factorsmentioning
confidence: 72%
“…Previous studies in Bay of Corme-Laxe detected severe contamination of the sediments by Cu (Prego et al, 2006), however a fuel oil origin was unlikely, with the major source of Cu being antifouling paints from the hulls of fishing vessels (Cobelo-García and Prego, 2003). Although contamination by Cu and Zn was observed in the uppermost sediment layers of the Prestige shipwreck area (Prego and Cobelo-García, 2004;Cobelo-García et al, 2005), this contamination is unlikely not be related to the shipwreck, because levels of Cu in the fuel oil carried by the Prestige were relatively low (3.39 mg kg À1 ) and previous studies have shown that inputs from terrestrial sources are probably higher than from the spilled fuel oil (Carballeira et al, 1997;Villares et al, 2007). Some of the studied variables demonstrate the stress of these contaminants and the effects on the benthic community; however, the results mostly point to chronic contamination with low bioavailability, and potential, but unconfirmed biological risk.…”
Section: Factor #3mentioning
confidence: 87%
“…Anthracene, fluoranthene, and pyrene showed acute toxicity in marine invertebrate embryos and larvae (Pelletier et al 1997(Pelletier et al , 2000. In general, exposure to high concentrations of PAHs is harmful to the exposed organisms who can bioaccumulate (1992) y se cuantificaron por espectrometría de absorción atómica de grafito (Perkin-Elmer 4100 ZL) (Cobelo-García et al 2005). Los resultados se expresaron en mg kg -1 de peso seco.…”
Section: Discussionunclassified
“…To determine trace metals (Ni, V, Cd, Pb, Cr, Co), the sediments were digested as described by Loring and Rantala (1992), and quantified by graphite furnace atomic absorption spectrometry (Perkin-Elmer 4100 ZL) (Cobelo-García et al 2005). The results are given in mg kg -1 dry weight.…”
Section: Chemical Analysesmentioning
confidence: 99%